Biomass Estimation of Eaglewood (Aquilaria filaria (Oken) Merr.) in the Karst Ecosystem of West Papua - Andes Hamuraby Rozak; Zaenal Mutaqien; Destri Destri (Universitas Gadjah Mada, 2021)
Eaglewood is Indonesia’s important trade commodity in the form of resins from several infected species of Thymelaeaceae. The basis to determine its international trade quota through CITES is derived from the estimated eaglewood-producing species grown in their habitat. This paper aims to estimate the biomass of eaglewood, Aquilaria filaria, in the karst ecosystem of West Papua. We conducted a plot-based method and calculated the biomass of A. filaria using a diameter-based allometric equation and simulated using a bootstrap procedure. The results showed that 15,500 tons of naturally infected eaglewood are estimated in the karst ecosystem of West Papua.